The relationship of inflation and GDP growth rate and fixed deposit interest rate in Nepal: An analytical study - Sapkota, Ashutosh Sharma (A Bi-annual South Asian Journal of Research & Innovation, 2025)
The impact of inflation and GDP on fixed deposit rates in Nepal is a critical area of study given its implications for financial stability and economic growth. Due to regulatory guidelines, banks are publishing different interest rates for individuals and institutions. Institutional deposits form major part of fixed deposit in Nepal and is highly skewed towards one year term. Historically, inflation affects deposit rates by eroding the real returns that depositors receive, thereby requiring higher rates to maintain depositor interest. On the other hand, GDP growth can affect these rates by altering the economic environment in which banks operate. A growing GDP generally promotes increased economic activity and investment opportunities, potentially resulting in changes to the demand for deposits and the rates offered. This research explores how these macroeconomic factors influence the fixed deposit interest rates, particularly fixed deposit rates of one year’s tenor by examining 10 year quarterly historical data and applying suitable econometric models. The study indicates that unlike in other developing countries, GDP and inflation in Nepal has no statistically significant impact on 1-year fixed deposit rates. Policy makers must look for other factors and explore other tools for effective transmission of monetary policies to stabilize the fixed deposit rates. The banks in Nepal should explore other instruments of different tenor and nature for reducing the dependency on fixed deposits as sources of funds as better strategy. Similarly, depositors should be able to make better investment decisions to real interest rates to negate the inflation impact.